O ensino de História no ciclo de alfabetização das escolas municipais de Vitória da Conquista, Bahia (2010 – 2014) - Santos, Isaac Cardoso (2016)
This study deals with the teaching of History in Literacy cycle, specifically about the place of this discipline in the process of children's literacy in Vitoria da Conquista county, Ba (20102014). We have analyzed the National Pact for Literacy at the Right Age (NPLRA), a federal program, which expresses the importance of a diversified curriculum for this cycle, composed of all the areas that composes the curriculum, the use of this Program justifies in the time frame, as we analyze our object before and after the accession in Bahia county to NPLRA. For this, we work with literacy women teachers, coordinators of the Municipal Secretary of Education (MSE) of the aforementioned and school coordinators. We have analyzed the conception of literacy of these professionals because we believe that it directly influences in the direction that school gives to the scholar discipline History. In this sense, we also analyzed the express curriculum and the real curriculum for the concerned discipline and the initial training and continuing training of literacy teachers. We use a diversified corpus documentary that includes: official documents of the Department of Education for the cycle we studied; express curriculum and Decennial Plan of Education of Vitoria da Conquista / BA 2008-218 , project of four Education Degree Course, courses programming and discipline menus that deals with methodology and History teaching in these courses, questionnaire applied with coordinators of SME and transcribed interviews with literacy teachers and school coordinators teachers . We use classic researchers who are dedicated to teaching History, such as Abud (2007), Bittencourt (2009), Cerri (2011) and Fonseca (2009). Our work is guided by the principles of Cultural History and the oral method and is based on the principles of qualitative research. We realize that the school discipline History still holds a supporting place in the scenario of star literacy process by duet between Portuguese and Mathematics.